Sustainability as an ecology of learning, thinking and acting: Using the World Health Organization's six P's as an action-research intervention to create public value with multiple bottom lines. (August 2019) - Amhøj, Christa Breum
This paper elaborate on how sustainabilising entails rethinking about areas that include rationality, organisations, knowledge, leadership and value and about transforming these areas into an ecological way of thinking, learning and acting. We argue that sustainability needs to become a verb, something we do. However, one thing is rethinking areas; another thing is to work it into a craft of research. Therefore, the second section in the paper unfolds a conceptualisation of a specific action-learning project in Danish municipalities, called 'Sustainable and Healthy Cities through Urban Nature Relations'. This project transforms the theoretically rethinking of sustainability into a craft of research. Informed by the proposed theoretical lens, the action-learning process involves research based on the World Health Organization's six P's (people, place, participation, peace, prosperity and planet). The action research can be understood as a process of taking risks, becoming disorientated and moving beyond the comfort zone. However, the six P's and thereby the cross-professional groups, the place, the participation and the value of the process is all about collective techniques and about care. It aims to create an emerging ecology of practices and of belonging and co-existing lives. It creates a field of actions a 'milieu' but without a fixed horizon.